ANALYSIS OF THE IMPLEMENTATION OF TAX ALLOWANCE FACILITIES IN THE INDONESIA SHIP AND BOAT INDUSTRY - Matondang, Yogi Michael; Asqolani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This research aims to analyze the implementation of the tax allowance facility in attracting investment in the ship and boat industry. This is because not a single ship and boat industry business actor has utilized the tax allowance facility in Indonesia since 2007 until now. The research method used is qualitative research. Secondary data collection was carried out through a literature review and interviews. The data were then analyzed using the public policy implementation model developed by Grindle (1980). The research found that the utilization of this facility by the business actors in the ship and boat industry will not yield significant economic benefits. The ship and boat industry also faces fundamental problems. These things make the tax allowance facility unattractive. Moreover, policy socialization has not been carried out optimally, meaning that information regarding the existence of this policy has not reached business actors in the ship and boat industry.